Teachers - Deedrick, Tami (Mankato, Minnesota : Capstone Press, 1998)
Explains the tools, schooling, and work of teachers.
Includes bibliographical references and index.
Keywords: Teachers -- Juvenile literature; Teaching -- Vocational guidance -- Juvenile literature